ImmunoFISH: Simultaneous Visualisation of Proteins and DNA Sequences Gives Insight Into Meiotic Processes in Nuclei of Grasses - Sepsi, Adél; Fábián, Attila; Jäger, Katalin; Heslop-Harrison, J. S.; Schwarzacher, Trude (Frontiers in Plant Science, 2018)
ImmunoFISH is a method combining immunolabelling with fluorescent in situ hybridization to simultaneously detect the nuclear distribution of proteins and specific DNA sequences within chromosomes. This approach is particularly important when analysing meiotic cell division where morphogenesis of individual proteins follows stage-specific changes and is accompanied by a noticeable chromatin dynamism. The method presented here is simple and provides reliable results of high quality signal, low background staining and can be completed within 2 days following preparation. Conventional widefield epi-fluorescent or laser scanning microscopy can be used for high resolution and three-dimensional analysis. Fixation and preparation techniques were optimized to best preserve nuclear morphology and protein epitopes without the need for any antigen retrieval. Preparation of plant material involved short cross-linking fixation of meiotic tissues with paraformaldehyde (PFA) followed by enzyme digestion and slide-mounting. In order to avoid rapid sample degradation typical of shortly fixed plant materials, and to be able to perform immunolabelling later, slides were snap-frozen and stored at -80 °C. Ultra-freezing produced a remarkable degree of structural preservation for up to 12 months, whereby sample quality was similar to that of fresh material. Harsh chemicals and sample dehydration were avoided throughout the procedure and permeability was ensured by a 0.1-0.3% detergent treatment. The ImmunoFISH method was developed specifically for studying meiosis in Triticeae, but should also be applicable to other grass and plant species